VALIDATING A KNOWLEDGE MANAGEMENT ORIENTATION CONSTRUCT IN THE PRIVATE UNIVERSITIES CONTEXT IN JORDAN: AN EMPIRICAL STUDY - Bani Doumi, Fakhri A. I. (International Journal of Research -GRANTHAALAYAH, 2022)
This study is an attempt to validate one of the knowledge managements constructs that is called knowledge management orientation (KMO), which was proposed and validated already by Wang and Ahmed (2004). The reason for this revalidation of the f KMO construct is to work in a different context where it will be applied to measure knowledge management performance in the private universities in Jordan. To achieve this, a random sample of 296 managerial position employees was selected from different private universities in Jordan, where confirmatory factor analysis was applied to test for model fit. The results revealed a modified model with only 19 items rather than the initial 30 items, where all the five factors remain the same. As for reliability and validity, the analysis shows the quality of measurement by conducting Internal and composite Reliability and Convergent and Discriminant validity.